Nature and treatment outcomes of bleeding post‐bulbar duodenal ulcers. Issue 5 (26th October 2021) - Matsuhashi, Tamotsu; Fukuda, Sho; Abe, Yasuhiko; Mikami, Tatsuya; Tatsuta, Tetsuya; Hikichi, Takuto; Nakamura, Jun; Onozato, Yusuke; Hatta, Waku; Masamune, Atsushi; Ohyauchi, Motoki; Ito, Hirotaka; et al.
Abstract : Background: Although post‐bulbar duodenal ulcers (PBDUs) could become a source of upper gastrointestinal bleeding, the whole picture of the disease is unknown. We compared the characteristic features and treatment outcomes after endoscopic hemostasis between PBDUs and bulbar duodenal ulcers (BDUs). Methods: Data on duodenal ulcers with evidence of endoscopically‐active bleeding were extracted from the data that were retrospectively collected from 12 institutes in Japan between 2011 and 2018. Rebleeding and in‐hospital mortality were compared between patients with PBDUs and those with BDUs by logistic regression analyses. Results: Among 468 consecutive patients with bleeding duodenal ulcers, 96 (20.5%) had endoscopically‐confirmed PBDUs. PBDUs were more frequently observed in patients with a poor general condition in comparison to BDUs. The rates of rebleeding and in‐hospital mortality in patients with PBDUs were approximately three times higher than those in patients with BDUs (PBDU vs. BDU: 29.2% vs. 10.2% [ P <  0.0001] and 14.6% vs. 5.1% [ P =  0.0029], respectively). Although the high in‐hospital mortality in PBDUs could be explained, to a lesser extent, by the likelihood of rebleeding, and, to a greater extent, by the patients' poor general condition, the presence of a PBDU itself was largely responsible for the high rebleeding rates in PBDUs. Conclusion: This is the first study focusing on the nature and treatment outcomes of bleeding PBDUs. PBDUs were associated with much higher rebleeding and mortality rates in comparison to BDUs, and the likelihood of rebleeding may be derived from their unique anatomic location.